ECOLOGIES OF SUBVERSION AND INSPIRATION ON TWITTER: THE HIJACKING OF #MYNYPD - Breideband, Thomas (AoIR Selected Papers of Internet Research, 2015)
Recent new media image scandals on Twitter such as the #myNYPD hashtag debacle in 2014 or the #McDStories hashtag controversy in 2012 have pointed towards emancipatory, anti-corporate communication practices of engaged citizens and customers surrounding the acquisition of social capital online. In view of these events, I argue that communication practices of resistance on new media reinforce and strengthen the complementary and reciprocal relationship between structure and agency. By analyzing cases of hashtag hijacking, we can see new media’s transgressive potential for individuals and groups to participate in ad hoc communities of protest and to appropriate, manipulate, and redirect particular hashtag conversations through ecologies of subversion and inspiration. Internet researchers can, thus, not only demarcate various rhetorical roles exercised by individual participants but also trace the impact of hashtags as idiosyncratic, discourse-enabling markers.